Răspuns :
Răspuns:
6+2[(3·5²-2²·18:3²+3·11):2²]=
6+2[(3·25-4·18:9+3·11):4]=
6+2[(75-8+33):4]=
6+2(100:4)=
6+2·25=
6+50=
56
Răspuns: [tex]\bf \red{\underline{~56~}}[/tex]
[tex]\bf 6 + 2 \cdot [(3 \cdot 5^2 - 2^2 \cdot 18 : 3^2 + 3 \cdot 11) : 2^2] =[/tex]
[tex]\bf 6 + 2 \cdot [(3 \cdot 25 - 4 \cdot 18 : 9 + 3 \cdot 11) : 4] =[/tex]
[tex]\bf 6 + 2 \cdot [(75 - 72 : 9 + 33) : 4] =[/tex]
[tex]\bf 6 + 2 \cdot [(75 - 8 + 33) : 4] =[/tex]
[tex]\bf 6 + 2 \cdot [(67 + 33) : 4] =[/tex]
[tex]\bf 6 + 2 \cdot (100 : 4) =[/tex]
[tex]\bf 6 + 2 \cdot 25 =[/tex]
[tex]\bf 6 + 50 =[/tex]
[tex]\bf \red{\underline{~56~}}[/tex]